Biofertilizers and chemical fertilizer application for increasing the growth and yield of foxtail millet (Setaria italica (L.) P. Beauv.) in a pot experiment - Reginawanti Hindersah; Andina Chotimah; Asana Matsuura; Yeni Wispa Dewi; Agung Karuniawan (Jurnal AGRO, 2023)
Biofertilizers are recommended to improve crops yield but researches regarding biofertilizer inoculation on foxtail millet in Indonesia is still Tlimited. The objective of the experiment was to analyze the growth and yield responses of five local-millet accessions to Bacillus biofertilizer with reduced NPK fertilizer dose; and the germination rate of millet seeds. The pot experiment was arranged in randomized block design with 10 treatments and 10 replications. The treatments were combination of five millet accessions with one dose of NPK fertilizer, and half dose of NPK fertilizer with biofertilizer. Generally, half dose of NPK with Bacillus inoculation did not change the height of six-weeks old plant, and panicle weight and length of millet compared to one dose of NPK. However, this combined fertilizer increased plant height and panicle length of Mani-Mani 79. Reduced dose NPK with Bacillus inoculation increased panicles number of J3 but reduced that of Polman 3; moreover, this combined fertilizer increased the grain weight of J3 and J4, but decreased the yield of Polman 3. The Enrekang and Polman 3 accession had better germination rate; 92% and 89.33%, respectively. This research considered that Bacillus biofertilizer reduced NPK fertilizer dose by 50% and is suggested for growing millet.ABSTRAKPupuk hayati banyak disarankan untuk meningkatkan produksi tanaman tetapi riset mengenai inokulasi pupuk hayati pada jewawut aksesi lokal Indonesia belum banyak dilakukan. Percobaan ini bertujuan untuk menganalisis respons pertumbuhan dan hasil lima aksesi jewawut lokal terhadap inokulasi pupuk hayati Bacillus dan pengurangan dosis pupuk NPK; serta daya berkecambah biji jewawut setelah panen. Percobaan pot disusun dalam rancangan acak kelompok dengan 10 perlakuan dan 10 ulangan. Perlakuan percobaan adalah kombinasi lima aksesi jewawut dengan satu dosis pupuk NPK, dan setengah dosis pupuk NPK disertai pupuk hayati. Umumnya, tinggi tanaman umur enam minggu, serta bobot dan panjang malai jewawut dengan setengah dosis NPK disertai inokulasi Bacillus sama dengan tanaman yang diberi satu dosis NPK. Namun, tinggi tanaman dan panjang malai Mani-Mani 79 meningkat setelah aplikasi setengah dosis NPK dengan inokulasi Bacillus. Jumlah malai aksesi J3 meningkat sedangkan Polman 3 menurun dengan aplikasi setengah dosis NPK disertai inokulasi Bacillus. Kombinasi pupuk ini meningkatkan bobot biji J3 dan J4 tetapi  menurunkan hasil Polman 3. Aksesi Enrekang dan Polman 3 memiliki daya berkecambah yang lebih baik; masing-masing sebesar 92% dan 89,33%. Penelitian ini menunjukkan bahwa pupuk hayati Bacillus dapat mengurangi dosis pupuk NPK sampai 50% dan dapat disarakan untuk tanaman jewawut.